Knowledge and attitude of nurse professionals towards medical waste management at Hamad Medical Corporation in Qatar: a cross-sectional study - Musa, Fatema; Mohamed, Ayatullah A.; Selim, Nagah (International Journal Of Community Medicine And Public Health, 2020)
Background: The improper management of wastes generated in health care facilities can severely affect the health of caregivers, patients and members of the community. Medical waste management can be achieved with the cooperation of all workers and patients; however, nursing personnel play a significant role in the whole process. Therefore, this study was done to evaluate the knowledge of nursing professionals regarding waste management in Hamad Medical Corporation (HMC) hospitals in Doha and to assess their attitude towards medical waste management. Methods: Descriptive cross-sectional study conducted at 4 governmental hospitals in Doha city; Hamad General Hospital (HGH), Women’s Hospital (WH), Rumiallalh Hospital (RH) and Al-Amal hospital among 420 nurses. Results: The response rate among nurses were 82.3%, most of them are female and non-Qatari. On analyzing data on knowledge about waste management procedures, it was found that the most widely reported procedures was segregation (89.9%) and incineration (84.9%). Almost all nurses (99.4%) believed that training and education regarding medical waste is required for all staff, also 98.8% of the studied nurses agreed that attending medical waste management program is beneficial. Conclusions: Knowledge of most studied nurses regarding medical waste management was found to be high and had positive attitude.